MANAJEMEN ROUTER DAN MONITORING QoS BERBASIS MQTT PADA JARINGAN PRIVATE 4G FWA - Nabil Alrofi; aryanti aryanti; sopain soim (LPPM Universitas Abdurrab, 2026)
The advancement of wireless network technology has accelerated the implementation of Private 4G LTE as a reliable communication solution across various industrial sectors. This study implements router management using a MikroTik RB951Ui-2nD and a Quality of Service (QoS) monitoring system based on the MQTT protocol in a Private 4G Fixed Wireless Access (FWA) network. The MikroTik router was configured as a relay through static routing and Network Address Translation (NAT) masquerading to distribute Internet connectivity from the Core Network to all client devices. The monitoring system was developed using an MQTT broker and Node-RED to display real-time QoS parameters, including throughput, delay, jitter, and packet loss. Performance evaluation involved six (6) active users generating video streaming, social media, and online gaming traffic. The results show that the routing and NAT configuration could transmit Internet connectivity to all devices stably and without interruption. The MQTT- and Node-RED-based monitoring system displayed QoS data in real time with an average latency of 45 ms. Furthermore, the implementation of Simple Queue on the MikroTik router proved effective in improving network service quality, reducing delay by 26.99%, jitter by 30.36%, and packet loss by 48.57%. All measured QoS parameters remained within the thresholds defined by ITU-T Recommendation G.1010. These findings demonstrate that the integration of MikroTik, MQTT, and Node-RED provides an effective solution for the management and monitoring of Private 4G FWA networks.